2012
DOI: 10.1136/annrheumdis-2012-202328
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for diagnosis of carpal tunnel syndrome: comparison of different methods to determine median nerve volume and value of power Doppler sonography

Abstract: Sonographic assessment of median nerve swelling and vascularity allows for a reliable diagnosis of CTS. Determination of CSA at its maximal shape offers an easily reproducible tool for CTS classification in daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
130
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(138 citation statements)
references
References 26 publications
4
130
0
4
Order By: Relevance
“…Nevertheless, ethnicity, whether the patient is diabetic or not, age and body mass index play a role in deciding which level of measurement is more sensitive (Ahmad 2011, Coraci et al 2014Mondelli et al 2008;Paliwal et al 2014;Tsai et al 2013). Cross-sectional area sensitivity varies widely among studies, from 48% to 89% (Beekman and Visser 2003;Duncan et al 1999;El Miedany et al 2004;Yesildag et al 2004), and specificity varies from 62% to 100% (Ajeena 2013;Dejaco et al 2013;Picerno et al 2013). The CSA cutoff varies from 0.9 to 1.5 cm (Ahn et al 2009;Keles et al 2005;Wiesler et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ethnicity, whether the patient is diabetic or not, age and body mass index play a role in deciding which level of measurement is more sensitive (Ahmad 2011, Coraci et al 2014Mondelli et al 2008;Paliwal et al 2014;Tsai et al 2013). Cross-sectional area sensitivity varies widely among studies, from 48% to 89% (Beekman and Visser 2003;Duncan et al 1999;El Miedany et al 2004;Yesildag et al 2004), and specificity varies from 62% to 100% (Ajeena 2013;Dejaco et al 2013;Picerno et al 2013). The CSA cutoff varies from 0.9 to 1.5 cm (Ahn et al 2009;Keles et al 2005;Wiesler et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our and several previous studies demonstrated a high diagnostic value of ultrasound for carpal tunnel syndrome (CTS) 1 2. Among the various abnormalities within the carpal tunnel reported, the increase of the cross-sectional area (CSA) of the median nerve is the most commonly studied ultrasound abnormality 3.…”
mentioning
confidence: 73%
“…Among the various abnormalities within the carpal tunnel reported, the increase of the cross-sectional area (CSA) of the median nerve is the most commonly studied ultrasound abnormality 3. Additionally, ultrasound allows the identification of secondary causes of CTS, such as synovitis, tenosynovitis, calcified masses or tophaceous gout, as pointed out by zhu et al 4 We acknowledge that the diagnostic value of ultrasound is not perfect, as some patients may suffer from CTS despite a normal ultrasound result and, vice versa, abnormal ultrasound findings do not necessarily indicate CTS 1. In these cases, additional tests, such as nerve conduction studies (although the sensitivity and specificity of this method are far away from 100% as shown in our and several other studies) are required to establish the final diagnosis 1 5…”
mentioning
confidence: 99%
“…We read with great interest the report by Dejaco et al 1 related to diagnosis of carpal tunnel syndrome (CTS) by ultrasound. Dejaco et al compared ultrasound measurement of median nerve cross-sectional area (CSA) at different anatomical landmarks in great detail and evaluated the value of intranerval power Doppler signals for CTS diagnosis.…”
mentioning
confidence: 99%
“…The volume of median nerve should be measured on the 3D space image. However, Dejaco et al 1 measured CSA of nerves on the 2D image. In order to avoid ambiguity, we proposed to use the term ‘area’.…”
mentioning
confidence: 99%